Efficacy of vaccines prepared from Pasteurella multocida cells grown in chemically defined media - SRIVASTAVA, S K (The Indian Journal of Animal Sciences, 2013)
Pasteurella multocida serotype B: 2 was grown in chemically defined medium (COM), COM supplemented with iron (CDM.Fe) and brain heart infusion broth (BHIB) and studied for their imrnunogenicity. Cells grown in CDM expressed maximum outer membrane protein (OMP) as demonstrated by congo red binding property of the bacterial cells. These cells, when used as vaccine, afforded maximum protection (100%) in mice than cells grown in the CDM.Pe (78%) or BRIB (72%). In buffalo calves the CDM.Fe and BHIB grown cell vaccine elicited higher anti-protein passive haemagglutination antibody responses than the COM vaccine. Cells grown in COM. Fe were more agglutinogenic than the CDM or BHIB grown cells. The study suggested that P.multocida cells grown in COM or CDM.Fe media possessed different antigens resulting in higher seroreactivity.